Carbonic Anhydrase: An Efficient Enzyme with Possible Global Implications. (24th September 2013) - Boone, Christopher D.; Gill, Sonika; Habibzadegan, Andrew; McKenna, Robert
Abstract : As the global atmospheric emissions of carbon dioxide (CO2 ) and other greenhouse gases continue to grow to record-setting levels, so do the demands for an efficient and inexpensive carbon sequestration system. Concurrently, the first-world dependence on crude oil and natural gas provokes concerns for long-term availability and emphasizes the need for alternative fuel sources. At the forefront of both of these research areas are a family of enzymes known as the carbonic anhydrases (CAs), which reversibly catalyze the hydration of CO2 into bicarbonate. CAs are among the fastest enzymes known, which have a maximum catalytic efficiency approaching the diffusion limit of 10 8  M −1 s −1 . As such, CAs are being utilized in various industrial and research settings to help lower CO2 atmospheric emissions and promote biofuel production. This review will highlight some of the recent accomplishments in these areas along with a discussion on their current limitations.